Practicing traditional cultural games skills according to random and game-based practice schedules can improve gross motor skills performance - Cheong, Jadeera Phaik Geok; Hussain, Bahar (Frontiers in Psychology, 2024)
The aim of this research was to examine the effects of using a random and game-based practice schedule for Traditional Cultural Games (TCG) skills on the performance of gross motor skills. Specifically, skills of two types of TCG, Chindro, an individual TCG, and Pittu-Garam, a team TCG, were practiced. 102 primary school children, ages seven to ten, attended a total of eighteen sessions of skill practice in 6 weeks, practicing TCG motor skills found in the game of Chindro or Pittu-Garam. For each TCG, participants were assigned to either random or game-based conditions, contributing to four experimental groups (Chindro random, Chindro game-based, Pittu random, and Pittu game-based). Gross motor skills performance was measured, before and after the experiment, according to the Test of Gross Motor Development-2. Particularly, the performance of six gross motor skills, Catch, Overhead Throw, Underhand Roll, Hop, Leap, and Jump, were assessed. Additionally, through a transfer test, the same skills were evaluated from a real-world game situation. In the skills performance test, all four groups significantly improved gross motor skills performance by the end of the experiment. However, there was no difference found between the groups based on game-based and random selection in the skills performance test and the game transfer test for both TCG. Practicing TCG skills according to high interference practice schedules, whether individually or in combination, improved gross motor skills performance. The study indicated that a game-based practice schedule could be a substitute for a random practice schedule when planning a training session involving high-interference practice schedules.